The Development Of Learning-Based Guided Inquiry On Waste Materials To Enhance Students Learning Results students of SMK - Halimatus Sa’diyah (EDUCATIO : Journal of Education, 2018)
This study aims to develop proper learning material theoretically on the lesson plan, student worksheet, student handbook and pretest and posttest on the subject of waste management matter with student respond supporting science learning. This research uses part of Dick and Carey model and trial design using one group pretest-posttest design with quantitative descriptive, qualitative descriptive analysis techniques. The research conducted at the Critical Thinking, Creativity Nurul Huda Situbondo. Measured research parameter cover validity teaching material, the implementation of teaching material, The result of learning and student of response. The result of research showed that the developed teaching materials fall in average of validity suitable criteria, the learning mastery of students showed high value, the student’s response were included in excellent category, and the obstacles during learning process were caused by the student were never involved in learning process using guided inquiry so they felt as a new experience. Based on the result of data analysis, it can be concluded that learning material with guided inquiry used in course of study of IPA (biology) to increase the result of learning waste items.